1989
DOI: 10.1007/bf00271263
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function in newly diagnosed Type 2 (non-insulin-dependent) diabetic patients, before and during treatment

Abstract: Glomerular filtration rate, kidney volume, and urinary albumin excretion rate were studied in otherwise healthy newly diagnosed Type 2 (non-insulin-dependent) diabetic patients, untreated at diagnosis, after short-term treatment and after 3 months treatment. In 10 patients (Group A) glomerular filtration rate (measured by the plasma clearance of 51-Cr-EDTA) decreased from the time of diagnosis 106.2 +/- 14.6 ml.min-1.1.73 m2(-1) (mean +/- SD) to 95.9 +/- 13.7 ml.min-1.1.73 m2(-1) after 3 months treatment (p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
32
4

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 32 publications
8
32
4
Order By: Relevance
“…In IDDM each ofthese abnormalities has been more marked in the presence of uncontrolled hyperglycemia (4,5) and moderated by insulin treatment into a range similar to that observed in the modestly hyperglycemic subjects ofthe present study (6,18,29). Although measurable hyperfiltration could not be clearly demonstrated in an older population with NIDDM of recent onset, insulin treatment also resulted in a significant depression of GFR under these circumstances (30). Thus, the prevailing GFR appears to be related to the level of glycemia, both in insulin-and noninsulin-dependent diabetes mellitus.…”
Section: Discussionsupporting
confidence: 72%
“…In IDDM each ofthese abnormalities has been more marked in the presence of uncontrolled hyperglycemia (4,5) and moderated by insulin treatment into a range similar to that observed in the modestly hyperglycemic subjects ofthe present study (6,18,29). Although measurable hyperfiltration could not be clearly demonstrated in an older population with NIDDM of recent onset, insulin treatment also resulted in a significant depression of GFR under these circumstances (30). Thus, the prevailing GFR appears to be related to the level of glycemia, both in insulin-and noninsulin-dependent diabetes mellitus.…”
Section: Discussionsupporting
confidence: 72%
“…The high rates of hyperfiltration in new-onset diabetes may be explained, at least partly, by the acute metabolic effect of hyperglycaemia, as previous studies have demonstrated an association between hyperglycaemia and hyperfiltration as well as nephromegaly [23,24]. Improved glycaemic control has been shown to reduce GFR and kidney size [25,26] Long-term hyperglycaemia has also been correlated with elevated GFR in type 1 diabetes [27]. In contrast, we did not find any difference in glycaemic control between the age-unadjusted and -adjusted hyperfiltration and control groups.…”
Section: Discussionmentioning
confidence: 97%
“…Gilbert et al [30] reported a significant association between rate of change in UAE and HbAlc in progressors, but whether this was due to those with poor control having a higher average is unclear. Optimising glycaemic control reduces albuminuria at least in shortterm studies [12,[15][16], but the long-term consequences of such intervention are unknown in NIDDM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent microalbuminuria (i. e. a urinary albumin excretion (UAE) from 20 ~g/min to 200 ~g/min) in patients with IDDM defines the state of incipient nephropathy [3], which is the state from which approximately 80 % progress to overt nephropathy over the next decade. Microalbuminuria [4,[6][7][8][9][10][11], and often present at diagnosis or at early known durations [4,[11][12][13][14][15][16]. Microalbuminuria in NIDDM obviously do also predict the development of clinical proteinuria [17], which will progress in some cases to renal failure, but with far less consistency than is seen in IDDM [18].…”
mentioning
confidence: 99%